PENGARUH KEBUDAYAAN ASING DALAM PEMBENTUKAN RAGAM HIAS PELAMINAN NAREH PARIAMAN - Rahmanita, Nofi (CORAK, 2012)
The Handicraft of embroidery âpalaminanâ in Nareh Pariaman is an old culture product which is used for social purposes. As the time goes, now, the âpalaminanâ is not only used by the king or noblesse. Right now, it has been used in mostly wedding parties of Minangkabau tradition. It is used as the seat of the bride groom and bride who are called king and queen for a day. Regarding this theme, when we see the several various of palaminan, it looks like been influenced by the Chinese and Hindi/Gujarat Custom. Such as phoenix 9(bird) and lion decorated at the âpalaminanâ, or for the Gujarat custom, there are embroidery with mirrors that decorate the palaminan. The mirror embroidered for the people of Nareh Pariaman has the meaning âsuluah bendangâ in the village. The art of embroidery palaminan Nareh Pariaman has many structures which are connected to each other. They can not be separated in each use. The structures are decorated by the many kinds of Minangkabau decoration. Most of the decorating comes from application of the Minangkabauâsphilosophy known as âalam takambang Jadi Guruâ. The philosophy has symbolic meaning that contains some lessons about managing humans life, especially for people of Nareh Pariaman.Keywords: beyond culture, motif, pelaminan